Intervensi psikologi Islam: Model konseling kelompok dengan teknik self-management-tazkiyatun nafs - Agustin, Liliza (Asosiasi Psikologi Islam (API) Himpsi, 2018)
This study is a development method. In the background of efforts to create Islamic psychology interventions, the researcher designs a module of Group counselling of self-management with Tazkiyatun Nafsi. The intervention is a theistic psychological intervention which is a development of the group counselling of self-management technique model from Cormier & Nurius. The difference is conceptualization and intervention emphasis in several aspects. Group Counseling of Self-Management with Tazkiyatun Nafsi has a vertical dimension (theistic) that uses tazkiyatun nafsi values as a reference in changing students' minds, feelings and learning behaviour through practice and habituation which is packaged by M.A.B.I.T. The method development has done by combining the concept of group counselling of self-management with tazkiyatun nafsi container as a psychological intervention. For the future, Counseling group of self-management with tazkiyatun nafsi can be applied, carried out research, and can be considered as a single intervention or additional intervention, especially for Muslim students. Keywords: Group counselling, learning, behavior, purification.